Selenium single-wavelength anomalous diffraction de novo phasing using an X-ray-free electron laser - Hunter, Mark S. (Nat Commun, 2016)
Structural information about biological macromolecules near the atomic scale provides important insight into the functions of these molecules. To date, X-ray crystallography has been the predominant method used for macromolecular structure determination. However, challenges exist when solving structures with X-rays, including the phase problem and radiation damage. X-ray-free electron lasers (X-ray FELs) have enabled collection of diffraction information before the onset of radiation damage, yet the majority of structures solved at X-ray FELs have been phased using external information via molecular replacement. De novo phasing at X-ray FELs has proven challenging due in part to per-pulse variations in intensity and wavelength. Here we report the solution of a selenobiotinyl-streptavidin structure using phases obtained by the anomalous diffraction of selenium measured at a single wavelength (Se-SAD) at the Linac Coherent Light Source. Our results demonstrate Se-SAD, routinely employed at synchrotrons for novel structure determination, is now possible at X-ray FELs.